The tracheal tube: gateway to ventilator-associated pneumonia - Zolfaghari, Parjam S (BioMed Central, 2011)
Ventilator-associated pneumonia (VAP) is a major healthcare-associated complication with considerable attributable morbidity, mortality and cost. Inherent design flaws in the standard high-volume low-pressure cuffed tracheal tubes form a major part of the pathogenic mechanism causing VAP. The formation of folds in the inflated cuff leads to microaspiration of pooled oropharyngeal secretions into the trachea, and biofilm formation on the inner surface of the tracheal tube helps to maintain bacterial colonization of the lower airways. Improved design of tracheal tubes with new cuff material and shape have reduced the size and number of these folds, which together with the addition of suction ports above the cuff to drain pooled subglottic secretions leads to reduced aspiration of oropharyngeal secretions. Furthermore, coating tracheal tubes with antibacterial agents reduces biofilm formation and the incidence of VAP. In this Viewpoint article we explore the published data supporting the new tracheal tubes and their potential contribution to VAP prevention strategies. We also propose that it may now be against good medical practice to continue to use a 'standard cuffed tube' given what is already known, and the weight of evidence supporting the use of newer tube designs.